Novel Detection Methods Used in Conjunction with Affinity Chromatography for the Identification and Purification of Hydrolytic Enzymes or Enzyme Inhibitors from Insects and Plants - Konarev, Alexander V.; Lovegrove, Alison (IntechOpen, 2012)
None